Effects of the pintle injector on H2/air continuous rotating detonation wave in a hollow chamber. (21st May 2019) - Huang, Siyuan; Li, Yangpeng; Zhou, Jin; Liu, Shijie; Peng, Haoyang
Abstract: Series of experiments have been conducted in a hollow chamber with pintle injector to investigate the relationship between continuous rotating detonation (CRD) and tangential instability. The results show that the insertion length of pintle has great influence on the operation range of CRD. When it exceeds 10 mm, the CRD will be unrealizable. The influence of pintle diameter is finite. The deflagration in head recirculation zone and mixing delay lead to a poor quality of detonation waves. Three different propagation modes are presented. Most of the successful CRD in this work are single-wave mode. The highest frequency and velocity are 6.55 kHz and 2010.40 m/s, respectively. Two dominant peak one-wave mode (TDPO) has been observed and it is a fairly new one which has not been sufficiently studied. Sawtooth-wave mode is a critical mode which always shows around the lean limit. The intrinsic frequency of the combustion chamber has been calculated and compared with the experiment results. It shows great agreement with the frequencies of TDPO with the error less than 5%. This work shows the effects of the pintle injector on H2 /air CRD wave in a hollow chamber. And it will contribute to a better understanding of the relationship between CRD and tangential instability. Highlights: Realizing rotating detonation in a hollow chamber with pintle injector. Analyzing the effects of pintle configurations on rotating detonation. Introducing three propagation modes of rotating detonation. Comparing intrinsic frequency with experiment frequencies.